2019
DOI: 10.9734/jalsi/2019/v20i230079
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and Haematological Effects of Chrysophyllum albidum Supplemented Diet on Streptozotocin Induced Diabetic Rats

Abstract: Background: The use of food in the management of diseases is an established art of science. It is essentially important in the management of chronic diseases such as diabetes mellitus where cure is not certain. Objective: This study investigated the anti-diabetic and heamatological effects of Chrysophyllum albidum fruit-skin (CAFS) supplemented diet on streptozotocin induced diabetic rats. Methods: Diabetes mellitus was induced by a single intraperitoneal injection of 50 mg/kg streptozotocin (STZ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…Iron content of Ficus capensis was in the order root > leaf > seed > and stem. The level of iron in this work agreed with the work of Ujowundu et al[35] that found low iron in the seeds of Dacryodes eldulus but did not agree with the work of Ibrahim et al[36]. Iron performs several functions in the body.…”
supporting
confidence: 62%
“…Iron content of Ficus capensis was in the order root > leaf > seed > and stem. The level of iron in this work agreed with the work of Ujowundu et al[35] that found low iron in the seeds of Dacryodes eldulus but did not agree with the work of Ibrahim et al[36]. Iron performs several functions in the body.…”
supporting
confidence: 62%
“…However, treatment of diabetic rats with CAFS supplementation reversed the altered levels of plasma K + , Na + , HCO3and Clto near normal values, indicating the renal protective role of CAFS in diabetic rats. Our previous studies demonstrated that C. albidum fruit skin is a potent radical scavenging agent (Ibrahim et al, 2019a), hypolipidemic and hypoglycemic agents (Ibrahim et al, 2019b) and thus, suggests its protective role that could ameliorate the development of diabetic complications such as hepatopathy and nephropathy.…”
Section: Discussionmentioning
confidence: 98%
“…Previously, we reported the antioxidant effect of C. albidum fruit skin extracts that was associated with flavoniods and phenolic contents (Ibrahim et al, 2019a). In addition, the hypolipidemic and antihyperglycemic potentials of C. albidum fruit skin in STZ-induced diabetic rats was demonstrated (Ibrahim et al, 2019b). The aim of the present study was to explore the effect of C. albidum fruit skin supplementation on liver and kidney function parameters of STZ-induced diabetic rats.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations